(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Human rights implementation has remained a crucial task owing to its poor implementation together with the multiple other factors. The gross violation in the field of human rights India and the infliction of atrocities on the vulnerable section of society represent our inability and gross indifference towards the same. The infringement of human rights in India will be required to be seen through the cultural prism where the theoretical assumptions with regard to the caste, creed, sect, religion, gender, language and region are seen in a peculiar way that result into its ossification. Despite of having laws at its disposal, the intrinsic loopholes permits it’s being loose and lost. What is required is to spread awareness and sensitize society for its being effective. The present paper takes a dig at understanding the human rights apropos of Indian constitution and also compares the human freedom of individuals Indian citizens to that of principle of human rights enshrines in the Universal Declaration of Human Rights (UDHR). The paper further throws light on challenges before India with reference to human rights implementation.